The impact of COVID-19 induced lockdown on the changes of air quality and land surface temperature in Kolkata city, India - Sahani, Nemai (Spat. Inf. Res., 2020)
The COVID-19 pandemic and related lockdown reduced the pollution level in the major megacities worldwide. The air pollution level of the city directly influences the air temperature and also land surface temperature (LST). In this paper, authors analyzed the impact of lockdown due to COVID-19 pandemic on the pollution level of the city and resulted LST. Single channel algorithm has been used to retrieve LST from Landsat Thematic Mapper satellite data. Pre-lockdown and post-lockdown satellite data has been used to show the changes in LST due to lockdown. The air quality index of pre-lockdown and post-lockdown period of the city estimated based on seven pollutants such as PM(2.5), PM(10), NO(2), NH(3), SO(2), CO and Ozone. The pollution level of the city and LST significantly decreased after lockdown is enforced. The pollution level of the major portion of the city before lockdown is moderately polluted (95–153 µm) and after lockdown the satisfactory level of pollution level observed (33–45 µm). The mean LST before lockdown is 28.76 °C (13 March, 2020) and it decreased down to 26.56 °C after lockdown (30 April, 2020). There is a sharp decrease of low value of LST observed (23.6–17.35 °C) in the city.